Поселения хазарского времени (Северо-Восточное Приазовье, Донецкий Кряж, степное Подонцовье) - Кравченко, Э.Е. (Археологический альманах, 2013)
Статья посвящена картографированию степных кочевий хазарского времени. Предлагается классификация и описание основных видов памятников, а также карта их распространения. В статті розглядаються середньовічні поселення Північного Приазов’я, Донецького Кряжу і степового Подонців’я, які були залишені кочовим населенням. Вказуються приблизні кордони поширення пам’яток цього типу. На підставі порівняння їх з матеріалами, що походять з осілих поселень середньої течії р. Сіверський Донець, акцентуються істотні відмінності цієї групи пам’яток від пам’яток, залишених осілим населенням салтово-маяцької культури. Піднімається питання про західний кордон Хозарського каганату на пізньому етапі його історії. The paper analyzes the nomadic medieval settlements from the Northern Azov Sea Littoral, Donetsk Ridge, and steppes of Severskiy Donets reaches. The author outlines the approximate borders of location of monuments of this type. The author also compared these monuments with findings from sedentary settlements of the Middle reaches of Severskiy Donets river and stressed on essential differences of this group of monuments from the monuments of the settled population of Saltov-Maiaki culture. The question of the western border of the Khazarian Qağanate at the late stage of its history is debatable.